ADMINISTRATION IN ACCORDANCE WITH GOOD GOVERNANCE OF THONG MONGKHON SUBDISTRICT ADMINISTRATIVE ORGANIZATION, BANG SAPHAAN DISTRICT, PRACHUAP KHIRI KHAN PROVINCE - Homdang, Prachum; Sartngern, Phachara (Journal of MCU Phetchaburi Review, 2025)
This mixed methods research aimed to 1) study the level of administration of Thong Mongkol Subdistrict Administrative Organization, 2) study the differences between personal characteristics that have opinions towards the administration of Thong Mongkol Subdistrict Administrative Organization, 3) study the causal relationship between good governance and administration, and 4) study the guideline for developing the administration based on the principle of good governance of Thong Mongkol Subdistrict Administrative Organization. The sample consisted of 390 people living in Thong Mongkol Subdistrict Administrative Organization and 8 key informants. Data were analyzed using percentage, mean, standard deviation, t-test, one-way variance, multiple regression, and content analysis. The results of the study found that 1) the administration of Thong Mongkol Subdistrict Administrative Organization was at a high level. 2) Different personal characteristics, including age, education level, occupation, and marital status, had different opinions towards the administration at the 0.05 significance level. 3) The principle of good governance, in terms of the principle of value for money, had a causal relationship with the administration at the 0.001 significance level, as did the rule of law, the principle of participation, and the principle of responsibility. There is a cause-and-effect relationship with management at a significance level of 0.01 in terms of morality and transparency. There is a cause-and-effect relationship with management at a significance level of 0.05. And 4) Guidelines for developing management according to the principles of good governance found that there should be a plan for operations based on people's problems. The organization should be organized according to the chain of command. There should be work performed according to the orders of the executives. There should be good coordination. There should be supervision of operations to be in accordance with the plan.